2021
DOI: 10.1111/ans.17163
|View full text |Cite
|
Sign up to set email alerts
|

The doctor will see you now: eye gaze, conversation and patient engagement in the surgical outpatient clinic. An Australian observational cross‐sectional study

Abstract: Background Surgical outpatient consultations are demanding for the surgeon and patients without a definite formula for success. Various factors have been identified regarding factors that influence patient satisfaction and engagement. We aimed to examine the modern‐day surgical outpatient consultation and report on these factors. Methods An observational cross‐sectional study was performed by reviewing video recordings of 182 surgical consultations by 12 surgeons at The Queen Elizabeth Hospital, South Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Remaining characteristics of the study have been previously reported. 12 A total of 3472 questions were asked. In consultations without companions (134/182), 1968/2407 questions were asked by the consultants (81.8%) compared to 439/2407 questions asked by patients (18.2%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remaining characteristics of the study have been previously reported. 12 A total of 3472 questions were asked. In consultations without companions (134/182), 1968/2407 questions were asked by the consultants (81.8%) compared to 439/2407 questions asked by patients (18.2%).…”
Section: Resultsmentioning
confidence: 99%
“…The mean consultation time was 12 min and 17 s (±8 min 12 s). Remaining characteristics of the study have been previously reported 12 . A total of 3472 questions were asked.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation